Evaluation of selected aspects of the hygiene hypothesis and their effect on the incidence of allergy - Edyta Krzych-Fałta; Oksana Wojas; Konrad Furmańczyk; Diana Dziewa-Dawidczyk; Barbara Piekarska; Bolesław Samoliński; Adam Sybilski (International Journal of Occupational Medicine and Environmental Health, 2023)
Objectives The development of allergic conditions is largely dependent on the interactions between genetic (individual genetic predisposition) and environmental factors (exposure to risk factors). The aim of this study was an attempt to assess the influence of selected elements of the hygiene theory in the development of allergic diseases such as allergic rhinitis and asthma.